Persons unknown - York, Jake Adam (Crab Orchard award series in poetry., 2010)
In this stunning continuation to the poetry collection A Murmuration of Starlings, dedicated to those who lost their lives during the Civil Rights movement, Jake Adam York presents another set of searing portraits of these martyrs-men whose murders haunt America's history. These elegiac and documentary poems seek justice and understanding for such sacrifices as Mack Charles Parker, lynched in Mississippi in 1959, his body disposed of in the waters of the Pearl River; Charles Eddie Moore and Henry Hezekiah Dee, abducted into the depths of the Homochitto Forest.